Effects of high loading rate on reinforced concrete beams - Fujikake, Kazunori (2014)
The majority of past research on reinforced concrete (RC) beams has focused on their behavior under static and relatively slow loading rates, while limited attention has been paid to the corresponding behavior under high loading rates. Thus, a comprehensive literature review has been conducted on RC beams under varying loading rates to observe the overall trend of dynamic increase factor (DIF) of maximum resistance and failure modes. The wide range of data pertaining to DIF and the apparent changes in failure modes means, however, that general agreement has yet to be reached among researchers. To supplement the limited literature in this field, 24 RC beams were tested under four different loading rates ranging from slow (4 × 10–4 m/s) to fast (2 m/s) to cover the wide range of loading scenarios (quasi-static, earthquakes, and impact regime). Comparative analyses of RC beams under these varying loading rates highlighted several key aspects of their dynamic behavior.